CONCEPTUAL MODEL FOR FLOOD PREDICTION USING THE TANK MODEL CASE STUDY: CIKAPUNDUNG WATERSHED - Radhika
In Indonesia, there are 5,590 main rivers and 600 of them have the potential to cause flooding. The flood-prone areas covered by these main rivers reach 1.4 million hectares. When rainfall is high, runoff is the most important component of the river outlet in a watershed; subsurface currents and groundwater account for a fraction of the flow of rivers. Large rainfall events usually create large surface runoff and cause a high probability of flooding in downstream areas, endangering the lives and property of individuals who live there. In this condition, hydrological analysis tends to focus on surface runoff simulations. This study aims to build a conceptual tank model to predict flooding, be it hydrograph form, peak time and flood volume and also be able to separate fast flow from slow flow using the routing transformation function, namely the gamma function. The model developed is good enough to predict flooding with an average correlation result 92% and an average NSE 0.86.